2014
DOI: 10.1111/2041-210x.12247
|View full text |Cite
|
Sign up to set email alerts
|

Rarefaction and extrapolation of phylogenetic diversity

Abstract: Summary1. Traditional species diversity measures do not make distinctions among species. Faith's phylogenetic diversity (PD), which is defined as the sum of the branch lengths of a phylogenetic tree connecting all species, takes into account phylogenetic differences among species and has found many applications in various research fields. In this paper, we extend Faith's PD to represent the total length of a phylogenetic tree from any fixed point on its main trunk. 2. Like species richness, Faith's PD tends to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

4
6

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 28 publications
1
91
0
1
Order By: Relevance
“…However, because diversity, or evolutionary history, is distributed unequally between taxa as well as between areas, taking into consideration only traditional species diversity may not be sufficient to fully capture differences among species (Chao et al, 2014). Therefore, to quantify biodiversity the focus shifted from pure species counting to a more integrative approach that quantifies the evolutionary information represented within groups of taxa (i.e.…”
Section: Phylogenetic Diversitymentioning
confidence: 99%
“…However, because diversity, or evolutionary history, is distributed unequally between taxa as well as between areas, taking into consideration only traditional species diversity may not be sufficient to fully capture differences among species (Chao et al, 2014). Therefore, to quantify biodiversity the focus shifted from pure species counting to a more integrative approach that quantifies the evolutionary information represented within groups of taxa (i.e.…”
Section: Phylogenetic Diversitymentioning
confidence: 99%
“…Consistent sampling is required to eliminate error or correction for the lowest sample size will often be necessary, resulting in a loss of information and sensitivity (but see Dornelas et al 2013). Recent advances have provided robust methods that correct for sampling biases in estimates of phylogenetic diversity (e.g., Chao et al 2015). van Zonneveld et al (2014) concluded that the number of 'locally common' alleles (defined as alleles restricted to a limited area of a species' distribution, but having high frequencies in these areas) may also be good indicators of overall genetic diversity.…”
Section: What To Monitor?mentioning
confidence: 99%
“…The rarefaction formula for Faith's PD was developed by Nipperess and Matsen (2013) and Nipperess (chapter "The Rarefaction of Phylogenetic Diversity: Formulation, Extension and Application"). Recently, Chao et al (2015) derived an integrated sampling, rarefaction, and extrapolation methodology to compare Faith's PD of a set of assemblages. Like species richness, Faith's PD does not consider species abundances.…”
Section: Introductionmentioning
confidence: 99%